Penggunaan Media Audio Visual dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran Mendengarkan Dialog Interaktif Siswa Kelas IX: Use of Audio Visual Media in Improving Student Learning Outcomes in Learning Listening to Interactive Dialogue of Class IX Students - Sakila Sakila (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This writing is motivated by problems in learning to listen to interactive dialogue in class IX. The problem is the difficulty of students in making conclusions. One reason is that the teacher has not used the media in learning. This writing aims to describe the improvement in the ability to listen to interactive dialogue by using audio-visual media for grade IX students in the odd semester of junior high school. Writing problem is how to improve students' skills in learning listening to interactive dialogue using audio visual media. To solve the problem and the purpose of writing is used descriptive method with library study data collection method. The writing results illustrate that the ability of students in learning to listen to interactive dialogue using audio-visual media has increased. From the results of the writing it can be concluded that the use of audio-visual media can be used as an alternative to improve students' skills in listening to interactive dialogue.